Emerging Cultural Conflicts in Italy: A Challenge for Criminal Law - Muzzica, Raffaele; Tamborra, Tracy L.; Amarelli, Giuseppe (International Journal of Criminology and Sociology, 2015)
Because of recent and rapid increases in immigration rates, Italy has been confronted with new forms of cultural conflicts. Cultural conflicts have resulted in cultural offenses; these are acts committed and promoted by people belonging to a minority culture that are considered to be offenses by the majority controlled legal system. In addition to defining cultural offenses and presenting defenses that are presented when cultural offenses are tried, this paper highlights pros, cons and potential pitfalls of considering culture under Italian law. Finally, suggestions to improve legal considerations of cultural diversity in Italy are presented; specifically the creation of laws to exculpate offenders of minor cultural offenses, the prioritization of justifications over excuses as a legal defense, and mitigated punishments in cases of major cultural offenses.